Earnings Management: A Case of Related Party Transactions - Maigoshi, Zaharaddeen Salisu; Latif, Rohaida Abdul; Kamardin, Hasnah (International Journal of Economics and Financial Issues, 2016)
This study was conducted on the related party transaction and earnings management. Agency theory provides that managers may engage into self-enrichment transactions to maximize their benefits at the detriment of the shareholders of the firm. Though, management or concentrated ownership was suggested as the possible solution to this problem, this form of ownership structure has its peculiar problems which are termed as type II agency problem. Controlling shareholders are found to be using their voting power to extract extra benefits from the firm through the insider information and in many instances engage in detrimental related party transactions at the expense of minority shareholders. This study have identified how and why controlling shareholders or managers use related party transaction as a means to perpetrate accrual-based or real activity earnings management. It was recommended that empirical study be conducted to investigate whether disclosure regulation can constrain the controlling shareholders or management against the use of real-activity management through related party transaction. Keywords: Related Party Transactions, Accrual-Based Earnings Management and Activity-Based Earnings Management. JEL Classifications: G34, G38, G180